Hope found, hope lost – eschatological aspects in the interpretations of Israelites’ wilderness wanderings. Two sides of one story: Origen’s 27. Homily on the Book of Numbers and Jerome’s Letter 78 - Wysocki, Marcin (Vox Patrum, 2017)
The writings of Origen and Jerome, which are the source of the article, although in a different literary form – a homily and a letter – and written for a different purpose and at different times, both are exegesis of the chapter 33 of the Book of Numbers in which the stops of the Israelites in the desert on the road to the Promised Land are described. Both texts are the classic examples of allegorical interpretation of the Scripture. Both authors interpret the 42 “stages” of Israel’s wilderness wanderings above all as God’s roadmap for the spiritual growth of individual believers, but there are present as well eschatological elements in their interpretations. In the presented paper there are shown these eschatological ideas of both authors included in their interpretations of the wandering of the Chosen People on their way to the Promised Land, sources of their interpretations, similarities and differences, and the dependence of Jerome on Origen in the interpretation of the stages, with the focuse on the idea of realized eschatology, present in Alexandrinian’s work. Origen has presented in his interpretation a very rich picture of the future hope, but Jerome almost nothing mentioned in his letter about hopes of the way towards God after death.